Temperature effects on the egg development time and hatching success of three Acartia Species(Copepoda: Calanoida) from the Strait of Malacca - Yoahida, T.; Liong, C.F.; Majid, A.M.; Toda, T.; Othman, B.H.J. (2012)
Temperature effects on the egg development time and hatching success of three Acartia species(Copepoda: Calanoida) from the Strait of Malacca. Zoological Studies 51(5): 644-654. Development times and hatching success rates at 6 temperatures (10, 14, 18, 22, 27, and 31°C) are presented for eggs of 3 congeneric Acartiid copepods, Acartia spinicauda, A. erythraea, and A. pacifica, from the Strait of Malacca, Malaysia. Egg development times of the 3 species were significantly related to the incubation temperature and each fit Bělehrádek’s function. Hatching success at 10°C was the lowest (13%) and significantly differed from those at other temperatures (by an ANOVA). Average hatching success rates at 14-31°C were 61% ± 26%, 78% ± 8%,and 87% ± 8% for A. erythraea, A. pacifica, and A. spinicauda, respectively. The temperature functions for egg development times of A. erythraea, A. pacifica, and A. spinicauda were D = 294(T - 4.47)-2.05, D = 545(T - 1.94)-2.05,and D = 352(T - 4.30)-2.05, respectively. Values of the ‘biological zero’ for Acartia were significantly correlated with environmental temperatures, suggesting that differences in temperature adaptation of development rates of eggs can be described from a single parameter of the temperature response. The results observed in this study were compared to findings from previous studies performed on other Acartiid species and from other copepod general